Chronic exposure to elevated nitrate concentrations alters behaviour in the swordtail fish, Xiphophorus hellerii - Meredith Fitschen-Brown; Shasta Kamara; Madison Parker; Kelsey Daniels; Anthony L. Gilbert; Molly R. Morris (Animal Behaviour, 2026)

Hydrogeology: Quo vadis…? A survey on the future of hydrogeology and seven ways forward in the light of global challenges - Christian Moeck; Olga Darazs; Andreas Ebert; Jannis Epting; Marie-José Gilbert; Sophie Gschwind; Jakob Helbing; Daniel Hunkeler; Pierre Yves Jeannin; Joaquin Jimenez-Martinez; Flavio Malaguerra; Lawrence Och; et al. (Hydrogeology Journal, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

PQRI Workshop: Model-Informed Drug Development (MIDD) Approaches in Pediatric Formulation Development - Gilbert J. Burckart; Susan Abdel-Rahman; Caleb Choi; M. Petrea Cober; James E. Cummins; Nikoletta Fotaki; Daniel Gonzalez; David Harris; Neil Parrott; Hardikkumar Patel; Fang Wu; Andreas Abend (The AAPS Journal, 2026)
In February of 2024, the Product Quality Research Institute held a virtual workshop entitled “Model-Informed Drug Development (MIDD) Approaches in Pediatric Formulation Development.” The workshop covered a range of topics related to pediatric formulation development and testing, including dissolution testing and applications to modeling drug absorption in developing pediatric patients. Workshop speakers reviewed the progress that has been made to advance our understanding of ontogeny related processes that drive interactions with product formulations and inform pediatric product development. They discussed recently constructed pediatric biorelevant models that provide more realistic information about drug dissolution in pediatric patients and their use in physiologically based models to produce data for regulatory submissions. Despite the progress, opportunities remain to expand the fund of knowledge on pediatric absorptive processes that will support the development of pediatric-friendly drug formulations. Graphical Abstract

Changes in Key Biodiversity Area networks following national comprehensive assessments - Andrew J. Plumptre; Zoltan Waliczky; Daniele Baisero; Olivia Crowe; Jeannot Kivono; Cecilia Tobar; Maria Gabriela Toscano; Natalia Boulad; Hugo Costa; Camila Davila; Sophie Dirou; Eleuterio Duarte; et al. (Conservation Biology, 2026)
Key Biodiversity Areas (KBAs) are sites of significance for the global persistence of biodiversity. Based on the Global Standard for the Identification of Key Biodiversity Areas (KBA Standard), published in 2016, sites are currently being assessed for KBA designation in a growing number of countries across the world. For these assessments, the KBA criteria are applied to all species and ecosystems with available data. We reviewed the first comprehensive assessments of 11 countries and compared the KBA network before and after assessments. The mean (SD) number of KBAs per country increased by 69.6% (102.1), and the mean total extent of KBAs per country increased by 164.2% (150.7). More than half of the KBAs in 2024 had >50% of their area outside the 2019 KBAs, indicating a substantial increase in KBA extent (54.0% [18.8] of KBAs). The mean proportion of each KBA covered by protected or conserved areas decreased from 56.2% (20.2) to 44.5% (15.5), owing to the incorporation of unprotected sites in the KBA network. On average, 41.1% (14.0) of sites in each country (mean 44.5 [46.4] sites per country) and 47.2% (20.5) of new KBA area after the assessment were completely unprotected, indicating that many of the new sites were not recognized in national protected area networks as significant for biodiversity before the assessment. Making a comprehensive assessment of KBAs increased the combined coverage of protected and conserved area networks from 25.4% (10.6) to 32.0% (13.1) in each country and thus contributed to reducing biodiversity loss. Therefore, comprehensive assessments of KBAs led to a substantially increased number and extent of recognized sites of importance for biodiversity published in the World Database of KBAs. Where such assessments have not been made, many important areas for biodiversity may be overlooked. We therefore encourage other nations to update their KBA networks to inform efforts to meet the goals and targets of the Kunming–Montreal Global Biodiversity Framework.

Potential of peatlands restoration for GHG emissions mitigation in France: Investigation of acquisition costs - Lise Pinault; Daniel Gilbert; Elsa Martin (Land Use Policy, 2025)

Resilient plants, sustainable future - Seung Y. Rhee; Daniel N. Anstett; Edgar B. Cahoon; Alejandra A. Covarrubias-Robles; Eric Danquah; Natalia Dudareva; Hiroshi Ezura; Kadeem J. Gilbert; Rodrigo A. Gutiérrez; Michelle Heck; David B. Lowry; Ron Mittler; et al. (Trends in Plant Science, 2025)

Host Species–Microbiome Interactions Contribute to Sphagnum Moss Growth Acclimation to Warming - Tatjana Živković; Alyssa A. Carrell; Gustaf Granath; A. Jonathan Shaw; Dale A. Pelletier; Christopher W. Schadt; Dawn M. Klingeman; Mats B. Nilsson; Manuel Helbig; Denis Warshan; Ingeborg J. Klarenberg; Daniel Gilbert; et al. (Global Change Biology, 2025)
Sphagnum moss is the dominant plant genus in northern peatlands responsible for long‐term carbon accumulation. Sphagnum hosts diverse microbial communities (microbiomes), and its phytobiome (plant host + constituent microbiome + environment) plays a key role in nutrient acquisition along with carbon cycling. Climate change can modify the Sphagnum ‐associated microbiome, resulting in enhanced host growth and thermal acclimation as previously shown in warming experiments. However, the extent of microbiome benefits to the host and the influence of host–microbe specificity on Sphagnum thermal acclimation remain unclear. Here, we extracted Sphagnum microbiomes from five donor species of four peatland warming experiments across a latitudinal gradient and applied those microbiomes to three germ‐free Sphagnum species grown across a range of temperatures in the laboratory. Using this experimental system, we test if Sphagnum 's growth response to warming depends on the donor and/or recipient host species, and we determine how the microbiome's growth conditions in the field affect Sphagnum host growth across a range of temperatures in the laboratory. After 4 weeks, we found that the highest growth rate of recipient Sphagnum was observed in treatments of matched host–microbiome pairs, with rates approximately 50% and 250% higher in comparison to maximum growth rates of non‐matched host–microbiome pairs and germ‐free Sphagnum , respectively. We also found that the maximum growth rate of host–microbiome pairs was reached when treatment temperatures were close to the microbiome's native temperatures. Our study shows that Sphagnum 's growth acclimation to temperature is partially controlled by its constituent microbiome. Strong Sphagnum host–microbiome species specificity indicates the existence of underlying, unknown physiological mechanisms that may drive Sphagnum 's ability to acclimatize to elevated temperatures. Together with rapid acclimation of the microbiome to warming, these specific microbiome–plant associations have the potential to enhance peatland resilience in the face of climate change.

Deuteration of non-labile protium in starch: Biosynthesis and characterisation from yeast-derived starch granules - Robert A. Russell; Lillian Caruana; Nageshwar Rao Yepuri; Daniel Oldfield; Thanh Ha Nguyen; Aditya Rawal; Elliot P. Gilbert (Carbohydrate Polymers, 2024)

The Relationship Between Maturation Size and Maximum Tree Size From Tropical to Boreal Climates - Valentin Journé; Michał Bogdziewicz; Benoit Courbaud; Georges Kunstler; Tong Qiu; Marie‐Claire Aravena Acuña; Davide Ascoli; Yves Bergeron; Daniel Berveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; et al. (Ecology Letters, 2024)
The fundamental trade‐off between current and future reproduction has long been considered to result in a tendency for species that can grow large to begin reproduction at a larger size. Due to the prolonged time required to reach maturity, estimates of tree maturation size remain very rare and we lack a global view on the generality and the shape of this trade‐off. Using seed production from five continents, we estimate tree maturation sizes for 486 tree species spanning tropical to boreal climates. Results show that a species' maturation size increases with maximum size, but in a non‐proportional way: the largest species begin reproduction at smaller sizes than would be expected if maturation were simply proportional to maximum size. Furthermore, the decrease in relative maturation size is steepest in cold climates. These findings on maturation size drivers are key to accurately represent forests' responses to disturbance and climate change.

Riverine concentrations and export of dissolved silicon, and potential controls on nutrient stoichiometry, across the land–ocean continuum in Great Britain - Andrew M. Tye; Helen P. Jarvie; Bryan M. Spears; Nancy B. Dise; Jennifer L. Williamson; Dan J. Lapworth; Don Monteith; Richard Sanders; Daniel J. Mayor; Michael J. Bowes; Michael Bowes; Annette Burden; et al. (Journal of Hydrology, 2024)

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

Understanding the risks of co-exposures in a changing world: a case study of dual monitoring of the biotoxin domoic acid and Vibrio spp. in Pacific oyster - Alle A. Y. Lie; Amity G. Zimmer-Faust; Rachel E. Diner; Emily Kunselman; Zachary Daniel; Kathryn Van Artsdalen; Mariana C. Salas Garcia; Jack A. Gilbert; Dana Shultz; Jeff Chokry; Kylie Langlois; Jayme Smith (Environmental Monitoring and Assessment, 2024)

Effect of amplitudes and frequencies on Virtual Planar Motion Mechanism of AUVs: Part II 3DOF implementation, comparison with RANSE and field trials - Lakshmi Madhavan Miller; Stephen Krauss; Stefano Brizzolara; Christine Gilbert; Daniel Stilwell (Ocean Engineering, 2023)

Ericoid shrub encroachment shifts aboveground–belowground linkages in three peatlands across Europe and Western Siberia - Alexandre Buttler; Luca Bragazza; Fatima Laggoun‐Défarge; Sebastien Gogo; Marie‐Laure Toussaint; Mariusz Lamentowicz; Bogdan H. Chojnicki; Michał Słowiński; Sandra Słowińska; Małgorzata Zielińska; Monika Reczuga; Jan Barabach; et al. (Global Change Biology, 2023)
In northern peatlands, reduction of Sphagnum dominance in favour of vascular vegetation is likely to influence biogeochemical processes. Such vegetation changes occur as the water table lowers and temperatures rise. To test which of these factors has a significant influence on peatland vegetation, we conducted a 3‐year manipulative field experiment in Linje mire (northern Poland). We manipulated the peatland water table level (wet, intermediate and dry; on average the depth of the water table was 17.4, 21.2 and 25.3 cm respectively), and we used open‐top chambers (OTCs) to create warmer conditions (on average increase of 1.2°C in OTC plots compared to control plots). Peat drying through water table lowering at this local scale had a larger effect than OTC warming treatment per see on Sphagnum mosses and vascular plants. In particular, ericoid shrubs increased with a lower water table level, while Sphagnum decreased. Microclimatic measurements at the plot scale indicated that both water‐level and temperature, represented by heating degree days (HDDs), can have significant effects on the vegetation. In a large‐scale complementary vegetation gradient survey replicated in three peatlands positioned along a transitional oceanic–continental and temperate–boreal (subarctic) gradient (France–Poland–Western Siberia), an increase in ericoid shrubs was marked by an increase in phenols in peat pore water, resulting from higher phenol concentrations in vascular plant biomass. Our results suggest a shift in functioning from a mineral‐N‐driven to a fungi‐mediated organic‐N nutrient acquisition with shrub encroachment. Both ericoid shrub encroachment and higher mean annual temperature in the three sites triggered greater vascular plant biomass and consequently the dominance of decomposers (especially fungi), which led to a feeding community dominated by nematodes. This contributed to lower enzymatic multifunctionality. Our findings illustrate mechanisms by which plants influence ecosystem responses to climate change, through their effect on microbial trophic interactions.

Hydrochemical and isotopic characteristics of the Lodwar Alluvial Aquifer System (LAAS) in Northwestern Kenya and implications for sustainable groundwater use in dryland urban areas - Florence Tanui; Daniel Olago; Gilbert Ouma; Zacharia Kuria (Journal of African Earth Sciences, 2023)

Food web structure and energy flux dynamics, but not taxonomic richness, influence microbial ecosystem functions in a Sphagnum-dominated peatland - Vincent E.J. Jassey; Owen L. Petchey; Philippe Binet; Alexandre Buttler; Geneviève Chiapusio; Frédéric Delarue; Fatima Laggoun-Défarge; Daniel Gilbert; Edward A.D. Mitchell; Janna M. Barel (European Journal of Soil Biology, 2023)

Biotic and Abiotic Control Over Diurnal CH4 Fluxes in a Temperate Transitional Poor Fen Ecosystem - Alexandre Lhosmot; Adrien Jacotot; Marc Steinmann; Philippe Binet; Marie-Laure Toussaint; Sébastien Gogo; Daniel Gilbert; Sarah Coffinet; Fatima Laggoun-Deffarge; Guillaume Bertrand (Ecosystems, 2023)

Linking seed size and number to trait syndromes in trees - Michal Bogdziewicz; Marie‐Claire Aravena Acuña; Robert Andrus; Davide Ascoli; Yves Bergeron; Daniel Brveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; Sergio Donoso Calderon; et al. (Global Ecology and Biogeography, 2023)
Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central America and East Asia. A minority of the data come from South America, Africa and Australia. Time period 1960–2022. Major taxa studied Trees. Methods We gathered 12 million observations of the number of seeds produced in 784 tree species. We estimated the number of seeds produced by individual trees and scaled it up to the species level. Next, we used principal components analysis and generalized joint attribute modelling (GJAM) to map seed number and size on the tree traits spectrum. Results Incorporating seed size and number into trait analysis while controlling for environment and phylogeny with GJAM exposes relationships in trees that might otherwise remain hidden. Production of the large total biomass of seeds [product of seed number and seed size; hereafter, species seed productivity (SSP)] is associated with high leaf area, low foliar nitrogen, low specific leaf area (SLA) and dense wood. Production of high seed numbers is associated with small seeds produced by nutrient‐demanding species with softwood, small leaves and high SLA. Trait covariation is consistent with opposing strategies: one fast‐growing, early successional, with high dispersal, and the other slow‐growing, stress‐tolerant, that recruit in shaded conditions. Main conclusions Earth system models currently assume that reproductive allocation is indifferent among plant functional types. Easily measurable seed size is a strong predictor of the seed number and species seed productivity. The connection of SSP with the functional traits can form the first basis of improved fecundity prediction across global forests.

Belize Blue Carbon: Establishing a national carbon stock estimate for mangrove ecosystems - Hannah K. Morrissette; Stacy K. Baez; Lisa Beers; Nadia Bood; Ninon D. Martinez; Kevin Novelo; Gilbert Andrews; Luis Balan; C. Scott Beers; Sumeet A. Betancourt; Reynel Blanco; Eeryn Bowden; et al. (Science of The Total Environment, 2023)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

A Global Ocean Oxygen Database and Atlas for Assessing and Predicting Deoxygenation and Ocean Health in the Open and Coastal Ocean - Marilaure Grégoire; Véronique Garçon; Hernan Garcia; Denise Breitburg; Kirsten Isensee; Andreas Oschlies; Maciej Telszewski; Alexander Barth; Henry C. Bittig; Jacob Carstensen; Thierry Carval; Fei Chai; et al. (Frontiers in Marine Science, 2021)
In this paper, we outline the need for a coordinated international effort toward the building of an open-access Global Ocean Oxygen Database and ATlas (GO 2 DAT) complying with the FAIR principles (Findable, Accessible, Interoperable, and Reusable). GO 2 DAT will combine data from the coastal and open ocean, as measured by the chemical Winkler titration method or by sensors (e.g., optodes, electrodes) from Eulerian and Lagrangian platforms (e.g., ships, moorings, profiling floats, gliders, ships of opportunities, marine mammals, cabled observatories). GO 2 DAT will further adopt a community-agreed, fully documented metadata format and a consistent quality control (QC) procedure and quality flagging (QF) system. GO 2 DAT will serve to support the development of advanced data analysis and biogeochemical models for improving our mapping, understanding and forecasting capabilities for ocean O 2 changes and deoxygenation trends. It will offer the opportunity to develop quality-controlled data synthesis products with unprecedented spatial (vertical and horizontal) and temporal (sub-seasonal to multi-decadal) resolution. These products will support model assessment, improvement and evaluation as well as the development of climate and ocean health indicators. They will further support the decision-making processes associated with the emerging blue economy, the conservation of marine resources and their associated ecosystem services and the development of management tools required by a diverse community of users (e.g., environmental agencies, aquaculture, and fishing sectors). A better knowledge base of the spatial and temporal variations of marine O 2 will improve our understanding of the ocean O 2 budget, and allow better quantification of the Earth’s carbon and heat budgets. With the ever-increasing need to protect and sustainably manage ocean services, GO 2 DAT will allow scientists to fully harness the increasing volumes of O 2 data already delivered by the expanding global ocean observing system and enable smooth incorporation of much higher quantities of data from autonomous platforms in the open ocean and coastal areas into comprehensive data products in the years to come. This paper aims at engaging the community (e.g., scientists, data managers, policy makers, service users) toward the development of GO 2 DAT within the framework of the UN Global Ocean Oxygen Decade (GOOD) program recently endorsed by IOC-UNESCO. A roadmap toward GO 2 DAT is proposed highlighting the efforts needed (e.g., in terms of human resources).

Animal Borne Ocean Sensors – AniBOS – An Essential Component of the Global Ocean Observing System - Clive R. McMahon; Fabien Roquet; Sophie Baudel; Mathieu Belbeoch; Sophie Bestley; Clint Blight; Lars Boehme; Fiona Carse; Daniel P. Costa; Michael A. Fedak; Christophe Guinet; Robert Harcourt; et al. (Frontiers in Marine Science, 2021)
Marine animals equipped with biological and physical electronic sensors have produced long-term data streams on key marine environmental variables, hydrography, animal behavior and ecology. These data are an essential component of the Global Ocean Observing System (GOOS). The Animal Borne Ocean Sensors (AniBOS) network aims to coordinate the long-term collection and delivery of marine data streams, providing a complementary capability to other GOOS networks that monitor Essential Ocean Variables (EOVs), essential climate variables (ECVs) and essential biodiversity variables (EBVs). AniBOS augments observations of temperature and salinity within the upper ocean, in areas that are under-sampled, providing information that is urgently needed for an improved understanding of climate and ocean variability and for forecasting. Additionally, measurements of chlorophyll fluorescence and dissolved oxygen concentrations are emerging. The observations AniBOS provides are used widely across the research, modeling and operational oceanographic communities. High latitude, shallow coastal shelves and tropical seas have historically been sampled poorly with traditional observing platforms for many reasons including sea ice presence, limited satellite coverage and logistical costs. Animal-borne sensors are helping to fill that gap by collecting and transmitting in near real time an average of 500 temperature-salinity-depth profiles per animal annually and, when instruments are recovered (∼30% of instruments deployed annually, n = 103 ± 34), up to 1,000 profiles per month in these regions. Increased observations from under-sampled regions greatly improve the accuracy and confidence in estimates of ocean state and improve studies of climate variability by delivering data that refine climate prediction estimates at regional and global scales. The GOOS Observations Coordination Group (OCG) reviews, advises on and coordinates activities across the global ocean observing networks to strengthen the effective implementation of the system. AniBOS was formally recognized in 2020 as a GOOS network. This improves our ability to observe the ocean’s structure and animals that live in them more comprehensively, concomitantly improving our understanding of global ocean and climate processes for societal benefit consistent with the UN Sustainability Goals 13 and 14: Climate and Life below Water. Working within the GOOS OCG framework ensures that AniBOS is an essential component of an integrated Global Ocean Observing System.

Modeling of levothyroxine in newborns and infants with congenital hypothyroidism: challenges and opportunities of a rare disease multi-center study - Gilbert Koch; Britta Steffens; Stephanie Leroux; Verena Gotta; Johannes Schropp; Pascal Gächter; Freya Bachmann; Tatjana Welzel; Marco Janner; Dagmar L’Allemand; Daniel Konrad; Gabor Szinnai; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2021)
Modeling of retrospectively collected multi-center data of a rare disease in pediatrics is challenging because laboratory data can stem from several decades measured with different assays. Here we present a retrospective pharmacometrics (PMX) based data analysis of the rare disease congenital hypothyroidism (CH) in newborns and infants. Our overall aim is to develop a model that can be applied to optimize dosing in this pediatric patient population since suboptimal treatment of CH during the first 2 years of life is associated with a reduced intelligence quotient between 10 and 14 years. The first goal is to describe a retrospectively collected dataset consisting of 61 newborns and infants with CH up to 2 years of age. Overall, 505 measurements of free thyroxine (FT4) and 510 measurements of thyrotropin or thyroid-stimulating hormone were available from patients receiving substitution treatment with levothyroxine (LT4). The second goal is to introduce a scale/location-scale normalization method to merge available FT4 measurements since 34 different postnatal age- and assay-specific laboratory reference ranges were applied. This method takes into account the change of the distribution of FT4 values over time, i.e. a transformation from right-skewed towards normality during LT4 treatment. The third goal is to develop a practical and useful PMX model for LT4 treatment to characterize FT4 measurements, which is applicable within a clinical setting. In summary, a time-dependent normalization method and a practical PMX model are presented. Since there is no on-going or planned development of new pharmacological approaches for CH, PMX based modeling and simulation can be leveraged to personalize dosing with the goal to enhance longer-term neurological outcome in children with the rare disease CH.

Correlation of cerebellar granular layer autolysis with ante-mortem systemic acid–base status - Apeksha N. Agarwal; Andrea R. Gilbert; Daniel D. Mais (Cell and Tissue Banking, 2021)

Hilfsmittel und Verfahren für zellbasiertes high content imaging - Daniel F. Gilbert; Oliver Friedrich; Christian Lesko; Kristin Hartmann (BIOspektrum, 2021)
Cell-based high content imaging has become a versatile and powerful method for studying e. g. cellular viability, morphology or physiology. However, high content imaging and its various applications require complex as well as expensive hardware and consumables, limiting its utility and usability. To broaden the applicability of cell-based high content imaging, we have developed tools and assaying techniques being exemplary portrayed in this article.

Enhancing air quality forecasts by geomatic downscaling: an application to daily PM10 concentrations in France - Daniel Joly; Daniel Gilbert; Maria Diaz-de-Quijano; Mohamed Hilal; Mathieu Joly; Nadine Bernard (Theoretical and Applied Climatology, 2021)

Historical isolation facilitates species radiation by sexual selection: Insights from Chorthippus grasshoppers - Zachary J. Nolen; Burcin Yildirim; Iker Irisarri; Shanlin Liu; Clara Groot Crego; Daniel Buchvaldt Amby; Frieder Mayer; M. Thomas P. Gilbert; Ricardo J. Pereira (Molecular Ecology, 2020)
Theoretical and empirical studies have shown that species radiations are facilitated when a trait under divergent natural selection is also involved in sexual selection. It is yet unclear how quick and effective radiations are where assortative mating is unrelated to the ecological environment and primarily results from sexual selection. We address this question using sympatric grasshopper species of the genus Chorthippus , which have evolved strong behavioural isolation while lacking noticeable ecomorphological divergence. Mitochondrial genomes suggest that the radiation is relatively recent, dating to the mid‐Pleistocene, which leads to extensive incomplete lineage sorting throughout the mitochondrial and nuclear genomes. Nuclear data shows that hybrids are absent in sympatric localities but that all species have experienced gene flow, confirming that reproductive isolation is strong but remains incomplete. Demographic modelling is most consistent with a long period of geographic isolation, followed by secondary contact and extensive introgression. Such initial periods of geographic isolation might facilitate the association between male signaling and female preference, permitting the coexistence of sympatric species that are genetically, morphologically, and ecologically similar, but otherwise behave mostly as good biological species.

Implications of different nitrogen input sources for potential production and carbon flux estimates in the coastal Gulf of Mexico (GOM) and Korean Peninsula coastal waters - Jongsun Kim; Piers Chapman; Gilbert Rowe; Steven F. DiMarco; Daniel C. O. Thornton (Ocean Science, 2020)
The coastal Gulf of Mexico (GOM) and coastal sea off the Korean Peninsula (CSK) both suffer from human-induced eutrophication. We used a nitrogen (N) mass balance model in two different regions with different nitrogen input sources to estimate organic carbon fluxes and predict future carbon fluxes under different model scenarios. The coastal GOM receives nitrogen predominantly from the Mississippi and Atchafalaya rivers and atmospheric nitrogen deposition is only a minor component in this region. In the CSK, groundwater and atmospheric nitrogen deposition are more important controlling factors. Our model includes the fluxes of nitrogen to the ocean from the atmosphere, groundwater and rivers, based on observational and literature data, and identifies three zones (brown, green and blue waters) in the coastal GOM and CSK with different productivity and carbon fluxes. Based on our model results, the potential primary production rate in the inner (brown water) zone are over 2 gC m−2 d−1 (GOM) and 1.5 gC m−2 d−1 (CSK). In the middle (green water) zone, potential production is from 0.1 to 2 (GOM) and 0.3 to 1.5 gC m−2 d−1 (CSK). In the offshore (blue water) zone, productivity is less than 0.1 (GOM) and 0.3 (CSK) gC m−2 d−1. Through our model scenario results, overall oxygen demand in the GOM will increase approximately 21 % if we fail to reduce riverine N input, likely increasing considerably the area affected by hypoxia. Comparing the results from the USA with those from the Korean Peninsula shows the importance of considering both riverine and atmospheric inputs of nitrogen. This has direct implications for investigating how changes in energy technologies can lead to changes in the production of various atmospheric contaminants that affect air quality, climate and the health of local populations.

Dispersal of a nearshore marine fish connects marine reserves and adjacent fished areas along an open coast - Diana S. Baetscher; Eric C. Anderson; Elizabeth A. Gilbert‐Horvath; Daniel P. Malone; Emily T. Saarman; Mark H. Carr; John Carlos Garza (Molecular Ecology, 2019)
Marine species with pelagic larvae typically exhibit little population structure, suggesting long‐distance dispersal and high gene flow. Directly quantifying dispersal of marine fishes is challenging but important, particularly for the design of marine protected areas (MPAs). Here, we studied kelp rockfish ( Sebastes atrovirens ) sampled along ~25 km of coastline in a boundary current‐dominated ecosystem and used genetic parentage analysis to identify dispersal events and characterize them, because the distance between sedentary parents and their settled offspring is the lifetime dispersal distance. Large sample sizes and intensive sampling are critical for increasing the likelihood of detecting parent–offspring matches in such systems and we sampled more than 6,000 kelp rockfish and analysed them with a powerful set of 96 microhaplotype markers. We identified eight parent–offspring pairs with high confidence, including two juvenile fish that were born inside MPAs and dispersed to areas outside MPAs, and four fish born in MPAs that dispersed to nearby MPAs. Additionally, we identified 25 full‐sibling pairs, which occurred throughout the sampling area and included all possible combinations of inferred dispersal trajectories. Intriguingly, these included two pairs of young‐of‐the‐year siblings with one member each sampled in consecutive years. These sibling pairs suggest monogamy, either intentional or accidental, which has not been previously demonstrated in rockfishes. This study provides the first direct observation of larval dispersal events in a current‐dominated ecosystem and direct evidence that larvae produced within MPAs are exported both to neighbouring MPAs and to proximate areas where harvest is allowed.

Obituary: Siv Aina Jensen Leendertz (Born Siv Aina Jensen: 1973–2018) - Chantal Akoua-Koffi; Sandra Beermann; Sébastien Calvignac-Spencer; Emmanuel Couacy-Hymann; Helene De Nys; Bernhard Ehlers; Thomas Gillespie; Jeffrey Gilbert; Jan F. Gogarten; Sandra J. Laney; Felix Lankester; Fabian H. Leendertz; et al. (International Journal of Primatology, 2018)

RECOTOX, a French initiative in ecotoxicology-toxicology to monitor, understand and mitigate the ecotoxicological impacts of pollutants in socioagroecosystems - Christian Mougin; Véronique Gouy; Vincent Bretagnolle; Julie Berthou; Patrick Andrieux; Patrick Ansart; Marc Benoit; Michaël Coeurdassier; Irina Comte; Cécile Dagès; Laurence Denaix; Sylvie Dousset; et al. (Environmental Science and Pollution Research, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Evaluation of eDNA for groundwater invertebrate detection and monitoring: a case study with endangered Stygobromus (Amphipoda: Crangonyctidae) - Matthew L. Niemiller; Megan L. Porter; Jenna Keany; Heather Gilbert; Daniel W. Fong; David C. Culver; Christopher S. Hobson; K. Denise Kendall; Mark A. Davis; Steven J. Taylor (Conservation Genetics Resources, 2018)

Transposable Elements Mediate Adaptive Debilitation of Flagella in Experimental Escherichia coli Populations - Gordon R. Plague; Krystal S. Boodram; Kevin M. Dougherty; Sandar Bregg; Daniel P. Gilbert; Hira Bakshi; Daniel Costa (Journal of Molecular Evolution, 2017)

Microbial diversity and ecological networks as indicators of environmental quality - Battle Karimi; Pierre Alain Maron; Nicolas Chemidlin-Prevost Boure; Nadine Bernard; Daniel Gilbert; Lionel Ranjard (Environmental Chemistry Letters, 2017)

Maßgeschneiderte Methoden und Technologien für high content imaging - Daniel F. Gilbert (BIOspektrum, 2017)

Transcriptomic Profiling of Egg Quality in Sea Bass (Dicentrarchus labrax) Sheds Light on Genes Involved in Ubiquitination and Translation - Daniel Żarski; Thaovi Nguyen; Aurélie Le Cam; Jérôme Montfort; Gilbert Dutto; Marie Odile Vidal; Christian Fauvel; Julien Bobe (Marine Biotechnology, 2017)

Air pollution below WHO levels decreases by 40 % the links of terrestrial microbial networks - Battle Karimi; Caroline Meyer; Daniel Gilbert; Nadine Bernard (Environmental Chemistry Letters, 2016)

The Tosontsengel Mongolia world record sea‐level pressure extreme: spatial analysis of elevation bias in adjustment‐to‐sea‐level pressures - Gomboluudev Purevjav; Robert C. Balling; Randall S. Cerveny; Rob Allan; Gilbert P. Compo; Philip Jones; Thomas C. Peterson; Manola Brunet; Fatima Driouech; José Luis Stella; Bohumil M. Svoma; Daniel Krahenbuhl; et al. (International Journal of Climatology, 2015)
A World Meteorological Organization ( WMO ) committee evaluated the record sea‐level pressure ( SLP ) measurement of 1089.4 hPa on 30 December 2004 in Tosontsengel, Mongolia (1724.6 m). Although instrumentation and data collection procedures were properly followed according to the assessment of the committee, concern was raised regarding the reliability of SLP adjustment from such a high‐elevation station. This paper addresses this concern with a number of analyses that look at relationships between SLP extremes and corresponding station elevation and temperature. First, we selected data from stations extracted from the Integrated Surface Database ( ISD ‐Lite) of NOAA 's National Climate Data Center. A spatial analysis indicates that elevation shows little to no association ( R 2 values essentially zero) to extreme SLP . However, a second analysis between extreme SLP and air temperature indicates that high regionalism exists in spatial correlations (local R 2 ) between those two variables. This relationship to temperature is likely the result of differences in SLP adjustment formulae used around the world. Based on this analysis, on the need to differentiate the SLP values adjusted using extremely cold temperatures (and generally high elevation), and following past WMO SLP guidelines, the WMO Rapporteurs for Climate and Weather Extremes therefore have created two distinct SLP records: (a) highest adjusted SLP (below 750 m), currently 1083.3 hPa recorded on 31 December 1968 at Agata, Evenhiyskiy, Russia; and (b) highest adjusted SLP (above 750 m), currently 1089.4 hPa (by Russian method; 1089.1 hPa by WMO formula) on 30 December 2004 in Tosontsengel, Mongolia. Future WMO guidance regarding SLP adjustment may lead to re‐evaluation of this and other SLP records.

Quality and Safety Requirements for Sustainable Phage Therapy Products - Jean-Paul Pirnay; Bob G. Blasdel; Laurent Bretaudeau; Angus Buckling; Nina Chanishvili; Jason R. Clark; Sofia Corte-Real; Laurent Debarbieux; Alain Dublanchet; Daniel De Vos; Jérôme Gabard; Miguel Garcia; et al. (Pharmaceutical Research, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Business oriented EU human cell and tissue product legislation will adversely impact Member States’ health care systems - Jean-Paul Pirnay; Alain Vanderkelen; Daniel De Vos; Jean-Pierre Draye; Thomas Rose; Carl Ceulemans; Nadine Ectors; Isabelle Huys; Serge Jennes; Gilbert Verbeken (Cell and Tissue Banking, 2013)

Using testate amoeba as potential biointegrators of atmospheric deposition of phenanthrene (polycyclic aromatic hydrocarbon) on “moss/soil interface-testate amoeba community” microecosystems - Caroline Meyer; Dorine Desalme; Nadine Bernard; Philippe Binet; Marie-Laure Toussaint; Daniel Gilbert (Ecotoxicology, 2013)

Above‐ and belowground linkages in Sphagnum peatland: climate warming affects plant‐microbial interactions - Vincent EJ Jassey; Geneviève Chiapusio; Philippe Binet; Alexandre Buttler; Fatima Laggoun‐Défarge; Frédéric Delarue; Nadine Bernard; Edward AD Mitchell; Marie‐Laure Toussaint; André‐Jean Francez; Daniel Gilbert (Global Change Biology, 2013)
Peatlands contain approximately one third of all soil organic carbon ( SOC ). Warming can alter above‐ and belowground linkages that regulate soil organic carbon dynamics and C ‐balance in peatlands. Here we examine the multiyear impact of in situ experimental warming on the microbial food web, vegetation, and their feedbacks with soil chemistry. We provide evidence of both positive and negative impacts of warming on specific microbial functional groups, leading to destabilization of the microbial food web. We observed a strong reduction (70%) in the biomass of top‐predators (testate amoebae) in warmed plots. Such a loss caused a shortening of microbial food chains, which in turn stimulated microbial activity, leading to slight increases in levels of nutrients and labile C in water. We further show that warming altered the regulatory role of Sphagnum ‐polyphenols on microbial community structure with a potential inhibition of top predators. In addition, warming caused a decrease in Sphagnum cover and an increase in vascular plant cover. Using structural equation modelling, we show that changes in the microbial food web affected the relationships between plants, soil water chemistry, and microbial communities. These results suggest that warming will destabilize C and nutrient recycling of peatlands via changes in above‐ and belowground linkages, and therefore, the microbial food web associated with mosses will feedback positively to global warming by destabilizing the carbon cycle. This study confirms that microbial food webs thus constitute a key element in the functioning of peatland ecosystems. Their study can help understand how mosses, as ecosystem engineers, tightly regulate biogeochemical cycling and climate feedback in peatlands

Beware of the commercialization of human cells and tissues: situation in the European Union - Jean-Paul Pirnay; Alain Vanderkelen; Nadine Ectors; Christian Delloye; Denis Dufrane; Etienne Baudoux; Michel Van Brussel; Michael P. Casaer; Daniel De Vos; Jean-Pierre Draye; Thomas Rose; Serge Jennes; et al. (Cell and Tissue Banking, 2012)

Arbuscular Mycorrhizal Fungal Infectivity in Two Soils as Affected by Atmospheric Phenanthrene Pollution - Dorine Desalme; Geneviève Chiapusio; Nadine Bernard; Daniel Gilbert; Marie-Laure Toussaint; Philippe Binet (Water, Air, & Soil Pollution, 2012)

Evaluation of a microbiological screening and acceptance procedure for cryopreserved skin allografts based on 14 day cultures - Jean-Paul Pirnay; Gunther Verween; Bruno Pascual; Gilbert Verbeken; Peter De Corte; Thomas Rose; Serge Jennes; Alain Vanderkelen; Miriam Marichal; Walter Heuninckx; Daniel De Vos (Cell and Tissue Banking, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Glycerol treatment as recovery procedure for cryopreserved human skin allografts positive for bacteria and fungi - Gilbert Verbeken; Gunther Verween; Daniel De Vos; Bruno Pascual; Peter De Corte; Cornelia Richters; Arlette De Coninck; Diane Roseeuw; Nadine Ectors; Thomas Rose; Serge Jennes; Jean-Paul Pirnay (Cell and Tissue Banking, 2012)

Experimental climate effect on seasonal variability of polyphenol/phenoloxidase interplay along a narrow fen–bog ecological gradient in Sphagnum fallax - VINCENT E. J. JASSEY; GENEVIÈVE CHIAPUSIO; DANIEL GILBERT; ALEXANDRE BUTTLER; MARIE‐LAURE TOUSSAINT; PHILIPPE BINET (Global Change Biology, 2011)
Extracellular phenoloxidase enzymes play an important role in the stability of soil carbon storage by contributing to the cycling of complex recalcitrant phenolic compounds. Climate warming could affect peatland functioning through an alteration of polyphenol/phenoloxidase interplay, which could lead them to becoming weaker sinks of carbon. Here, we assessed the seasonal variability of total phenolics and phenoloxidases subjected to 2–3 °C increase in air temperature using open‐top chambers. The measurements were performed along a narrow fen–bog ecological gradient over one growing season. Climate warming had a weak effect on phenoloxidases, but reduced phenolics in both fen and bog areas. Multivariate analyses revealed a split between the areas and also showed that climate warming exacerbated the seasonal variability of polyphenols, culminating in a destabilization of the carbon cycle. A negative relationship between polyphenols and phenoloxidases was recorded in controls and climate treatments suggesting an inhibitory effect of phenolics on phenoloxidases. Any significant decrease of phenolics through repeatedly elevated temperature would greatly impact the ecosystem functioning and carbon cycle through an alteration of the interaction of polyphenols with microbial communities and the production of extracellular enzymes. Our climate treatments did not have the same impact along the fen–bog gradient and suggested that not all the peatland habitats would respond similarly to climate forcing.

Potential release of aluminum and other metals by food-grade aluminum foil used for skin allograft cryo preservation - Gilbert Verbeken; Dirck Schoeters; Gunther Verween; Daniel De Vos; Bruno Pascual; Peter De Corte; Kris Geukens; Arlette De Coninck; Diane Roseeuw; Thomas Rose; Serge Jennes; Jean-Paul Pirnay (Cell and Tissue Banking, 2011)

The Phage Therapy Paradigm: Prêt-à-Porter or Sur-mesure? - Jean-Paul Pirnay; Daniel De Vos; Gilbert Verbeken; Maia Merabishvili; Nina Chanishvili; Mario Vaneechoutte; Martin Zizi; Geert Laire; Rob Lavigne; Isabelle Huys; Guy Van den Mooter; Angus Buckling; et al. (Pharmaceutical Research, 2011)

Combining Ecological Classification Systems and Conservation Filters Could Facilitate the Integration of Wildlife and Forest Management - Eric K. Zenner; JeriLynn E. Peck; Kristen Brubaker; Benjamin Gamble; Carrie Gilbert; Daniel Heggenstaller; Jeanne Hickey; Kelly Sitch; Robbie Withington (Journal of Forestry, 2010)
Ecosystem management demands simultaneous consideration and integration of ecosystem services in monitoring, planning, and management activities, but specialization has led to independently developed traditions in wildlife biology and management and forestry. We drew on the literature to explore the use of filters in wildlife conservation and ecological classification systems in forest management and to ask the question, “Can combining these tools improve our integration of wildlife and forest management?” Although each tool has been successfully applied independently, relatively few examples still exist for their combined use. We conclude that this approach has potential for enhancing research, monitoring, and management in areas beyond wildlife management, including forest health.

Response of testate amoeba assemblages to environmental and climatic changes during the Lateglacial–Holocene transition at Lake Lautrey (Jura Mountains, eastern France) - Adeline A. J. Wall; Michel Magny; Edward A. D. Mitchell; Boris Vannière; Daniel Gilbert (Journal of Quaternary Science, 2010)
We tested the response of lacustrine testate amoebae (thecamoebians) to climate and environmental changes for the Lateglacial–Holocene transition. The palaeoenvironmental history of the study site (Lake Lautrey, Jura Mountains, eastern France) was previously established based on high‐resolution multi‐proxy studies of the same core. The present study is characterised by a high taxonomic resolution (54 taxa), inclusion of small species (down to 25 µm) and high total counts (>500 individuals per sample on average). Changes in the composition of testate amoeba assemblages (dominant species and assemblage structure), as well as in the accumulation rate (tests cm −2 a −1 ), corresponded to major climatic phases (i.e. Oldest Dryas, Bølling–Allerød Interstadial, Younger Dryas, Preboreal) as well as changes in organic matter inputs. Furthermore, decreases in the accumulation rate characterised minor short‐lived cooling events, such as Older Dryas event or Gerzensee oscillation. However, the Preboreal oscillation, which was well registered by other proxies at Lake Lautrey, could not be recognised in the testate amoeba record. This work demonstrates that lacustrine testate amoebae can be used for palaeoclimatic and palaeoecological reconstructions. Nevertheless, a better understanding of the relation between climate, organic matter and lacustrine testate amoebae requires further high‐resolution studies based on multi‐proxy approaches and the development of appropriate modern analogues. Copyright © 2010 John Wiley & Sons, Ltd.

Atmospheric heavy metal deposition in Northern Vietnam: Hanoi and Thainguyen case study using the moss biomonitoring technique, INAA and AAS - Hung Nguyen Viet; Marina Vladimirovna Frontasyeva; Thu My Trinh Thi; Daniel Gilbert; Nadine Bernard (Environmental Science and Pollution Research, 2010)

Vulnerability to epidemic malaria in the highlands of Lake Victoria basin: the role of climate change/variability, hydrology and socio-economic factors - Shem O. Wandiga; Maggie Opondo; Daniel Olago; Andrew Githeko; Faith Githui; Michael Marshall; Tim Downs; Alfred Opere; Christopher Oludhe; Gilbert O. Ouma; Pius Z. Yanda; Richard Kangalawe; et al. (Climatic Change, 2010)

Do parafluvial zones have an impact in regulating river pollution? Spatial and temporal dynamics of nutrients, carbon, and bacteria in a large gravel bar of the Doubs River (France) - Thomas Deforet; Pierre Marmonier; Dominique Rieffel; Nadia Crini; Patrick Giraudoux; Daniel Gilbert (Hydrobiologia, 2009)

Knowledge Recovery for Continental-Scale Mineral Exploration by Neural Networks - Laurent Bougrain; Maria Gonzalez; Vincent Bouchot; Daniel Cassard; Andor L. W. Lips; Frédéric Alexandre; Gilbert Stein (Natural Resources Research, 2003)

Chromosomal location and tissue expression of the gene encoding the adenovirus E1A-regulated transcription factor E4F in humans and mice - Robert J. Rooney; Rachael R. Daniels; Nancy A. Jenkins; Debra J. Gilbert; Kristen Rothammer; Stephan W. Morris; Douglas R. Higgs; Neal G. Copeland (Mammalian Genome, 1998)

Influence of the amino acid sequence on the MUC5AC motif peptide O-Glycosylation by Human gastric UDP-GalNAc:polypeptide N-acetylgalactosaminyltransferase(s) - Sylviane Hennebicq; Daniel Tetaert; Benoit Soudan; Arnold Boersma; Gilbert Briand; Colette Richet; Jean Gagnon; Pierre Degand (Glycoconjugate Journal, 1998)